Two new Xestia Hübner, 1818 species from China (Lepidoptera, Noctuidae) - Gyulai, P.; Ronkay, L.; Saldaitis, A. (Zootaxa, 2013)
Beginning with the fundamental works of Boursin (1954, 1963, 1964), Old World exploration of the genus Xestia (s. l.) Hübner, 1818 traditionally focused on reddish-brown species from the generally monsoon, high mountains Himalayan region (Hacker (1990), Yoshimoto (1995), Hreblay & Ronkay (1997, 1998, 1999), Hreblay et al., (1998) and Kononenko et al., (2012)). More recent investigation of the southeast and eastern Tibetan plateau in the drier high altitude of Sichuan and Yunnan provinces resulted in the discovery of seven new species of Xestia (s. l.) described by Gyulai at al.(2011). Two additional new species from this region collected by Irene and Alessandro Floriani and the third author are described herein.